Developing English Speaking Teaching Material Based on Project Based learning Spiritual Approaches at Senior High School Student of Islamic Boarding School Ulun Nuha Medan - Firmansyah, Firmansyah; Risnawaty (PT Inovasi Pratama Internasional, 2026)
An effort made in the era of globalization in an Islamic boarding school is to prepare English language skills for students by developing their English speaking skills. However, in reality, the English speaking skills of students are very low, especially at Islamic Boarding School Ulun Nuha Medan, even though they have studied for years. The Researcher tries to provide a solution by using Islamic-themed English teaching materials by using teaching materials based on Project-based Learning spiritual approaches so that students are motivated and more confident in communicating in English, because the teaching materials presented are in accordance with the environment and conditions of the boarding school which is an Islamic environment, so that the interest of students in learning English increases and English communication is created and what is expected by the author and the boarding school is achieved, namely the formation of an English-speaking environment every day.